Hubungan Partus Lama dan Anemia dalam Kehamilan dengan Kejadian Atonia Uteri pada Ibu Bersalin - yuni Asmilawati; Ida Ayu Made Mahayani; Halia Wanadiatri; Adib Ahmad Shammakh (Syntax Corporation Indonesia, 2023)
Atonia uteri is a state of weak tone or uterine contraction, which causes the uterus to be unable to close open bleeding from the site of placental implantation after the baby and placenta are born. Maternal mortality in Indonesia is still relatively high, one of the causes is postpartum bleeding, especially caused by uterine atonia. This study aims to find out the relationship of prolonged labor and anemia in pregnancy with the incidence of uterine atonia in women giving birth at the NTB Provincial Hospital. This study is observationally analytical using case-control design. The sampling technique is total sampling. The research sampel consisted of 60 samples with each case and control 30 samples that fit the inclusion and exclusion criteria. The data obtained were analyzed with the chi-square correlation test. The result of his study were obtained prolonged labor are 18(71,7%) and who were not prolonged labor 43 (71,7%). While respondents with anemia 34 (56,7%) and who were not anemia 26 (43,3%).There is relationship between prolonged labor with incidence of uterine atony in women giving birth with p-value 0,010 and with OR 4,971 more at risk of uterine atony and there is relationship between anemia in pregnancy with the incidence of uterine atony in women giving birth with p-value 0,037 and with OR 3,051more at risk of uterine atony. There is significant relationship between prolonged labor and anemia in pregnancy with the incidence of uterine atony in women giving birth in the NTB Provincial Hospital.